KAFÂATU AT-THULLABI BI QAWÂIDI AN-NAHWI WA-SHARFI WA’ALÂQATIHÂ LIQUDROTIHIM ‘ALA QIRÂATIL KUTÂBI AL-ASFARI (AT-TURATSI) - Iwan Hadi Saputra; Mustafa Bin Che Omar; Suparmanto Suparmanto (El-Tsaqafah : Jurnal Jurusan PBA, 2022)
This study aims to examine and discuss how the impact of understanding and mastery of students on the rules of nahwu and shorof and the learning process at the al-Majidiyyah NW Majidi Islamic boarding school, East Lombok. The research method used in this study is descriptive qualitative with data collection techniques using interviews and documentation. The results of this study are: 1) The learning process of nahwu and shorof in al-Majidiyyah Islamic boarding school NW Majidi is divided into two, namely there are inside the classroom, and some are outside the classroom or extracurricular activities. 2) Understanding and The students' mastery of the nahwu and shorof rules has a very good impact and effect on their ability and fluency in reading and understanding classical book literature or the yellow book, and also with their mastery of the nahwu and shorof rules further motivates them in reading the turats books which have been they don't understand this yet, 3) For students who already understand and master the nahwu-shorof rules more it is easy to answer every Arabic exam questions held by Madrasah Institutions and also their scores in each Arabic exam have an average of 80 to 90, 4) And lastly, with their ability to read the yellow book then it will make it easier for them to continue their studies to Islamic universities both domestically and abroad such as in the Middle East in Egypt, Yemen, Sudan and so on in all universities that use Arabic as their language of instruction.